Pediatric epidemiology - Kiess, Wieland 1958-; Bornehag, Carl-Gustaf; Gennings, Chris (Basel : Karger, 2018)
Pediatric epidemiology differs substantially from general epidemiology especially when it comes to ethical, developmental and societal aspects. This unique book addresses biological considerations and ethical and legal questions in dealing with pediatric and adolescent populations. Classic topics, such as how to recruit representative samples, how to deal with confounding variables, and how to work with genetic information are the core areas of the book are also in focus. Last but not the least, this volume adds to the current understanding of global trends in occurrence, transmission, and control of epidemic pediatric diseases. This book not only serves as a textbook for epidemiologists, pediatricians, geneticists, and child and public health specialists but is also a key reference for those embarking on pediatric cohort studies and epidemiological studies involving the pediatric population.
Keywords: NIÑOS -- ENFERMEDADES -- EPIDEMIOLOGÍA